Value orientation of future teachers - Arnaudova, Violeta; Angeloska Galevska, Natasha; Mustafa, Avzi (Yildiz Technical University, 2014)
Studying the values has great importance and relevance in today’s time. Continuing changes in the society demand continuing research of the social and human values. The purpose of the research is to determine the value orientation of the students - future teachers, to assess the hierarchy and importance of each value and to discover the differences in self-ranking of values in relation to ethnicity and gender. Method: The empirical research was made in April and May 2013. The sample is stratified and consists of 100 Macedonian students from the Faculty of Philosophy in Skopje and 70 Albanian students from the Faculty of Philology in Skopje and Faculty of Education in Tetovo. To examine the system of values we used the Schwartz scale as a psychological inventory with 29 descriptions of human behavior in everyday life. The respondents have to estimate how much their features correspond to the given descriptions and to mark it on the five-degree scale. Data are analysed with adequate quantitative procedures from the descriptive and inferential statistics. Results – Conclusions: Collected data give us information for the following ten types of universal values: security, hedonism, conformity, achievement, power, tradition, benevolence, universalism, self-direction and stimulation. The results are compared with those gained in similar research made in year 2000, providing a glimpse into how human values have changed between 2000 and 2013. Related to ethnicity, difference was statistically significant (p<0.05) only in some types of values, such as: security, hedonism, conformity, tradition, benevolence in favor of Albanians, and achievements, self-direction and stimulation, in favor of Macedonians. Regarding the gender as a variable, difference was statistically significant in favor of the ‘security’ of the male students.
Keywords: value scales, value orientation, students, teachers